Ketamine in treating opioid use disorder and opioid withdrawal: a scoping review - Shen, Mary R.; Campbell, Dylan E.; Kopczynski, Anika; Maddams, Samuel; Rosenblum, Naomi; Nigam, Kabir; Suzuki, Joji (Frontiers in Psychiatry, 2025)
IntroductionOpioid use disorder (OUD) continues to be a public health crisis in the United States, with mortality having doubled over the last twenty years, leading to significant economic cost, morbidity, and mortality. This has caused significant demand for novel therapeutics. Preliminary evidence demonstrates that ketamine may be helpful in treating OUD as well as serve as an adjunct during treatment of opioid withdrawal (OW).MethodsWe conducted a scoping review of two databases (PubMed and PsycINFO) for English language, peer-reviewed manuscripts reporting on use of ketamine in treatment of OUD or OW in humans, excluding protocols and reviews. The study was conducted in accordance with PRISMA guidelines.ResultsThe search yielded 998 studies. After duplicates were removed, 715 studies underwent title and abstract screening for inclusion in the review. Of those, 21 were further considered under full text review. Three studies were excluded due to wrong study design and ten were excluded due to the wrong indication, specifically the use of ketamine for treatment of pain rather than substance use disorder or withdrawal. Eight studies were included in the review, regarding treatment for OUD (n=2) and OW (n=6). In OUD, ketamine administration was helpful in reducing opioid cravings and opioid use. In OW, ketamine attenuated precipitated withdrawal symptoms and was used in several case series/studies as an adjunct to buprenorphine treatment.ConclusionIn summary, this review presents a baseline of literature supporting the use of ketamine in OUD and OW. However, more research is needed before widespread use.